Impact of induction immunosuppression on patient survival in heart transplant recipients treated with tacrolimus and mycophenolic acid in the current allocation era. Issue 8 (19th July 2019) - Amin, Alpesh A.; Araj, Faris G.; Ariyamuthu, Venkatesh K.; Drazner, Mark H.; Ayvaci, Mehmet U.S.; Mammen, Pradeep P.A.; Mete, Mutlu; Urey, Marcus A.; Tanriover, Bekir
Abstract: Background: The practice of induction therapy with either rabbit anti‐thymocyte globulin (r‐ATG) or interleukin‐2 receptor antagonists (IL‐2RA) is common among heart transplant recipients. However, its benefits in the setting of contemporary maintenance immunosuppression with tacrolimus/mycophenolic acid (TAC/MPA) are unknown. Methods: We compared post‐transplant mortality among three induction therapy strategies (r‐ATG vs IL2‐RA vs no induction) in a retrospective cohort analysis of heart transplant recipients maintained on TAC/MPA in the Organ Procurement Transplant Network (OPTN) database between the years 2006 and 2015. We used a multivariable model adjusting for clinically important co‐morbidities, and a propensity score analysis using the inverse probability weighted (IPW) method in the final analysis. Results: In multivariable IPW analysis, r‐ATG (HR = 1.23; 95% CI = 1.05‐1.46, P  = 0.01) remained significantly associated with a higher mortality. There was a trend toward having a higher mortality in the IL2‐RA (HR = 1.11; 95% CI = 1.00‐1.24, P  = 0.06) group. Subgroup analyses failed to show a patient survival benefit in using either r‐ATG or IL2‐RA among any of the subgroups analyzed. Conclusion: In this contemporary cohort of heart transplant recipients receiving TAC/MPA, neither r‐ATG nor IL2‐RA were associated with a survival benefit. On the contrary, adjusted analyses showed a significantly higher mortality in the r‐ATG group and a trend toward higher mortality in the IL2‐RA group. While caution is needed in interpreting treatment effects in an observational cohort, these data call into question the benefit of induction therapy as a common practice and highlight the need for more studies.